Design and Validation of Switchable Tracks for Superconducting Levitation Systems - Espenhahn, Tilo; Berger, Dietmar; Hameister, Stefan; Huhne, Ruben; Schultz, Ludwig; Nielsch, Kornelius (IEEE Transactions on Applied Superconductivity, 2017)
In the past years, different superconducting levitation systems were developed around the world. Most projects focused on optimizing the flux density in the working space of the superconductor in order to maximize the levitation force of the system. In general, these systems use tracks with permanent magnetic Halbach arrays or combine permanent magnets with steel yokes to maximize the usable flux density. Therefore, none of these tracks can easily be switched off to allow a safe crossing or to build a fast turnout switch without moving parts. A new track was designed containing permanent magnets and a YBCO-tape-coil to realize a fast switchable track. In this concept, the permanent magnets provide the flux used for levitation, whereas the coil controls the flux in the space above the track, where levitation usually takes place. The magnetic behavior of this new design was studied and improved with two-dimensional (2-D) and 3-D simulations. Afterwards, a demonstrator was built on which the induced magnetic field was measured in the different operation modes. The results of the measurements and the simulations indicate that the flux density above of the track might be controlled by the coil current. It was proven that the new track design generates magnetic fields comparable to the standard permanent magnetic track, whereas only residual fields are measured in inactive mode, which can be further reduced with negative coil currents.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High-temperature superconductors; large-scale systems; levitation systems; superconducting coils